Modeling and 3D simulation of ductile crack growth with non-local Gurson-based formulation - Pardoen, Thomas; Kaniadakis, Antonio; Nguyen, Van-Dung; Noels, Ludovic; Javangorouh, Sara; Besson, Jacques (European journal of mechanics, A, Solids, 2025)
The state of maturity of the micromechanics of ductile fracture is such that it is possible, today, to simulate extensive crack growth in 3D using a sophisticated physics-based description of the mechanisms of nucleation, growth and coalescence of voids within a non-local formulation. Here, different phenomena related to ductile crack growth are addressed in the context of fracture mechanics specimens. Structural integrity assessment of many critical components does indeed rely on predictive models of crack growth from pre-existing sharp defects. Two similar extended Gurson models are used, after comparison to cross-verify their numerical implementation, to generate results about the effect of plate thickness, plastic anisotropy and strain hardening. The variation of the fracture toughness increasing and then decreasing with thickness down to the plane strain regime is captured owing to the 3D nature of the simulations that captures the crack tip necking phenomenon. The non-local formulation introduces a length scale that sets the range over which the fracture toughness depends on thickness. Surprizingly, the thickness effect disappears when using homothetic geometries. The effect of plasticity anisotropy is shown to be particularly important when a crack grows in sheets exhibiting significant crack tip necking by impacting among other the plastic dissipation in the neck. A large strain hardening capacity enhances very much the fracture toughness, an effect that is amplified in 3D when crack tip necking takes place. These findings constitute only a limited set of answers to many remaining questions in the important field of ductile tearing, setting an ambitious roadmap for the years to come to the solid mechanics community. These questions are particularly important in the context of modern technologies such as H2 storage, additive manufacturing, new high strength metallic alloys development, and generation IV nuclear fission and fusion reactors to name a few. •3D simulations of ductile crack growth with non-local Gurson model.•Analysis of CT and DENT fracture mechanics specimens.•Significant effect of thickness, plastic anisotropy, strain hardening on toughness.•Roadmap for important subjects related ductile crack growth.